Hybrid fabrication of piezoelectric thick films using a sol-infiltration and photosensitive direct-patterning technique - Lee, Jin-Hyung; Lee, Jeong Hoon; Kim, Sang Kyung; Park, Hyung-Ho; Kim, Tae Song (SPRINGER, 2015)
We propose a hybrid fabrication technique for piezoelectric thick films using sol-infiltration and a direct-patterning process. To achieve the demands of high-density and direct-patterning at a low sintering temperature, a photosensitive lead zirconate titanate (PZT) solution was infiltrated into a lead zinc niobate-lead zirconate titanate (PZN-PZT) thick film. The direct-patterned PZT films were formed on a locally screen-printed thick film, using a photomask and UV light. By optimizing the thickness of the photosensitive PZT layer, the hybrid films that were prepared with a 120-s soaking time of PZT sol showed a very dense and uniform microstructure with a large grain size at a low sintering temperature of 800 A degrees C. It also had enhanced electrical properties. The measured remnant polarization (P-r) and coercive field (E-c) were 14.61 mu C cm(-2) and 24.16 kV cm(-1), respectively. The P-r value was over four times greater than those of the screen-printed films. We fabricated array-type piezoelectric resonators with direct-patterned PZN-PZT thick films to show the ability of the direct-patterning of the PZT thick film on a silicon wafer for actuator and sensor application, especially for mass production.
Keywords: FERROELECTRIC PROPERTIES; DENSIFICATION; CERAMICS